On the Degree-Based Topological Indices of the Tickysim SpiNNaker Model - Muhammad Imran; Muhammad Kamran Siddiqui; Ali Ahmad; Usman Ali; Nazia Hanif (Axioms, 2018)
Tickysim is a clock tick-based simulator for the inter-chip interconnection network of the SpiNNaker architecture. Network devices such as arbiters, routers, and packet generators store, read, and write forward data through fixed-length FIFO buffers. At each clock tick, every component executes a “read” phase followed by a “write” phase. The structures of any finite graph which represents numerical quantities are known as topological indices. In this paper, we compute degree-based topological indices of the Tickysim SpiNNaker Model ( T S M ) sheet.